Economics of grids, clouds, systems, and services : 14th International Conference, GECON 2017, Biarritz, France, September 19-21, 2017, Proceedings /: 14th International Conference, GECON 2017, Biarritz, France, September 19-21, 2017, Proceedings. (2017) - Unknown
No abstract available